Infrared and conductivity studies on blends of PMMA/PEO based polymer electrolytes - Osman, Z.; Ansor, N. M.; Chew, K. W.; Kamarulzaman, N. (2005)
Poly(methylmetacrylate)/poly(ethylene oxide) (PMMA/PEO) based polymer electrolytes were synthesized using the solution cast technique. Four systems of PMMA/PEO blends based polymer electrolytes films were investigated: